THE LANGUANGE VARIETIES ON SOEKARNO’S SPEECHES - juwariyah juwariyah; Siane Herawati (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2014)
Soekarno stands as one of the best orator and great charisma the world has ever had. His charm and talk emersed his people. Soekarno’s speeches considered as histories record document for his nation and world widely. This study was aimed at finding the languange variation on his speeches. This was a descripive qualitative research in which data was taken by documentation . The collected data was analyzed through three steps, i.e. data reduction, data description, and conlusion. The data are first categorise into unit, then the data are categorising relate to the relationship of problem of study, and third the data are integrated to find the theory. The finding of this study revealed that first, Soekarno Javanese language use as dialectical word considered as influence of his origin and social caste as Madya level. Soekarno’s education background has a reason for him to insert Dutch words. Second, finding of Formal and Informal Register of Soekarno revealed that his professional Jargon and good structure (e.g adding and omission of prefixes or suffixes) consider as formal, besides his Common Colloquial Word and Vulgarism consider as Informal register. Third, Soekarno is differ in style while deliver a speech, he is rather to be Casual and Intimate to the citizen, besides also Formal on behave generally to them. But Soekarno tends to use Frozen style to some particular person. Soekarno also use Frozen on opening his speech his speech infront of leader of other nations without concern what will he talks in the following lines of his speech. Even if might swear or blame them. Keywords:,,